2022
DOI: 10.1177/15589447221127332
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Antegrade Homodigital Neurovascular Island Flaps in Distal Fingertip Reconstruction: A Systematic Literature Review

Abstract: Background: Antegrade homodigital neurovascular island flaps (AHIFs) are a heterogeneous group of pedicled flaps used for reconstruction of traumatic digital detipping injuries. While numerous single-center studies have documented their use, there are no large or multicentre studies validating their efficacy, applicability, and functional outcomes. We performed a systematic review of the contemporary literature to establish the safety and functional outcomes of this technique. Methods: Electronic searches were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 76 publications
2
2
0
Order By: Relevance
“…As in the larger series, such as those of Foucher et al (1989) and Smith and Elliot (2000) and the systematic review performed by Castillo et al (2022), we found a low incidence of complications. In particular there were no cases of complete flap necrosis, despite most surgeons in our study not being experienced hand surgeons.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…As in the larger series, such as those of Foucher et al (1989) and Smith and Elliot (2000) and the systematic review performed by Castillo et al (2022), we found a low incidence of complications. In particular there were no cases of complete flap necrosis, despite most surgeons in our study not being experienced hand surgeons.…”
Section: Discussionsupporting
confidence: 76%
“…As in the larger series, such as those of Foucher et al. (1989) and Smith and Elliot (2000) and the systematic review performed by Castillo et al. (2022), we found a low incidence of complications.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations